Mineral Elements Analysis of Selected Ethnomedicinally Valued Plants From Assam, India - UPADHYAYA, SRISTISRI; KHATIWORA, ELIZA; SAIKIA, L.R. (Asian Journal of Chemistry, 2010)
Elemental compositions of the leaves of five ethnomedicinally important plants viz., Hydrocotyl javanica, Litsea polyantha, Melastoma malabathricum, Paederia foetida and Vitex nigundo were studied from Dibrugarh, India. The study revealed good percentage of mineral element in the plants. Nitrogen, phosphorus, potassium and magnesium are major constituents in comparison to calcium, zinc, copper and manganese in all the species. Since the aboriginal people of the study area are using these plants in their traditional health care system, cultivation and consumption of these plants should be encouraged for partial fulfillment of their nutritional requirement.